Blood cadmium levels increase prostate specific antigen and insulin-like growth factor-1 among cadmium exposed workers - Roestijawati, Nendyah; Maurits, Lintje Setyawati; Sugiyanto, Sugiyanto (Faculty of Medicine, Trisakti University, 2017)
BACKGROUNDCadmium (Cd) is a heavy metal that is classified as a human carcinogen (group IA), one of the cancers that it can cause being prostate cancer. The development of prostate cancer on a molecular basis involves oncogenes such as insuline-like growth factor-1 (IGF-1). Prostate cancer can be detected in the laboratory through the examination of prostate specific antigen (PSA). The present study aimed to determine the relationship of Cd levels with levels of PSA and IGF-1 in exposed and unexposed workers.METHODSThe study design was cross sectional. The subjects of the studycame from two groups of workers, ie. the group of Cd exposed workers who were welding shop workers and the group of unexposed workers who were office workers. The minimum samplesize was 85 people. The independent variable was blood Cd level. The dependent variables were PSA and IGF-1 levels. Blood Cd levels were measured by atomic absorption spectrometry (AAS), while PSA and IGF-1 were measured using ELISA. Data analysis was performed using the Mann-Whitney test and the Spearman correlation test.RESULTSMean blood Cd level in the exposed workers was 6.5 mg/L and in the unexposed workers 2.15 mg/L. There was a relationship between blood Cd and PSA levels (p<0.05) and between blood Cd levels and IGF-1 (p <0.05).CONCLUSIONSThere was a relationship of blood Cd with PSA and IGF-1 levels.among workers. PSA and IGF-1 could be a biochemical markers of disease control in cadmium exposed workers.